Household Credit, Global Financial Cycle, and Macroprudential Policies : Credit Register Evidence from an Emerging Country - Epure, Mircea (IMF Working Papers; Working Paper ;, 2018)
We analyze the effects of macroprudential policies on local bank credit cycles and interactions with international financial conditions. For identification, we exploit the comprehensive credit register containing all bank loans to individuals in Romania, a small open economy subject to external shocks, and the period 2004-2012, which covers a full boom-bust credit cycle when a wide range of macroprudential measures were deployed. Although household leverage is known to be a key driver of financial crises, to our knowledge this is the first paper that employs a household credit register to study leverage and macroprudential policies over a full economic cycle. Our results show that tighter macroprudential conditions are associated with a significant decline in household credit, with substantially stronger effects for foreign currency (FX) loans than for local currency loans. The effects on FX loans are higher for: (i) ex-ante riskier borrowers proxied by higher debt-service-toincome ratios and (ii) banks with greater exposure to foreign funding. Moreover, tighter macroprudential policy has stronger dampening effects on FX lending when global risk appetite is high and foreign monetary policy is expansionary. Finally, quantitative effects are in general larger for borrower rather than lender macroprudential policies.